Trust in Mediating The Relationship between Security and Feature Availability on Customer Statisfaction Using Mobile Banking - Muzayyana Khoirunnisa; Yudha Trishananto (IQTISHADUNA, 2023)
The growth of mobile banking in Indonesia continues to increase rapidly because theconvenience of users of mobile banking services is getting faster because mobile bankingservices are able to provide convenience in transactions. The purpose of this study is todetermine how much influence security and feature availability have on satisfaction usingmobile banking. which is mediated by trust in customers of Bank Syariah Indonesia KCP PatiSudirman 2. This research is a quantitative study with primary data obtained from the methodof distributing questionnaires to 100 respondents to customers of Bank Syariah Indonesia KCPPati Sudirman 2 through a questionnaire with purposive sampling. Based on the T test andPath Analysis shows that there is a positive and significant effect of security on satisfactionusing mobile banking, feature availability on satisfaction using mobile banking, trust insatisfaction using mobile banking, security (security) on trust, feature availability on trust. Andtrust is able to mediate the relationship between security (security) and satisfaction using mobilebanking. As well as trust being able to mediate the relationship between feature availability andsatisfaction using mobile banking.